The Disarming Virtue of Stanley Hauerwas - Wells, Samuel (Scottish journal of theology, 1999)
Stanley Hauerwas likes to be regarded as a theologian. He writes about ethics, and ethics is commonly thought to be about decisions. But he believes that the fundamental decision is God's decision to be in relationship with his creation and his people. He believes that out of the Christian narrative come particular habits and practices that shape the lives of Christians in a distinctive way. He believes that Christians proclaim the sovereignty of God and the imitation of Christ by the practice of peaceable engagement with the world. These convictions earn his ethics the epithets of theological, narrative, and nonviolent.